If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 5n + 5n = -15 Combine like terms: 5n + 5n = 10n 5 + 10n = -15 Solving 5 + 10n = -15 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 10n = -15 + -5 Combine like terms: 5 + -5 = 0 0 + 10n = -15 + -5 10n = -15 + -5 Combine like terms: -15 + -5 = -20 10n = -20 Divide each side by '10'. n = -2 Simplifying n = -2
| (X+43)+(2x-73)=180 | | (7q-7)+(5q-9)= | | 6x+1=3(2x+1)-x+8 | | x+-5y=-3 | | 10x^2-45x-25=0 | | X+11=5x-2 | | -64-(4x-14)=15 | | b+10=96 | | 6x+3+39=90 | | 4x-4x=-6 | | 7(x-6)=4 | | 8x+4=6x-4 | | X=-6-11 | | 70x+55b=14 | | 6(x+3)-(x+2)=27 | | -x+3+13x=-6+3x+54 | | 18y=9y+18 | | 5(x-4)+4(x-6)=7 | | 2-x+5=7-3 | | 5x+4+26=90 | | -x+2+7x=-2+2x+16 | | N^2+6n-21=0 | | 5m-4=2m-22 | | 22x+22(x-9)=45 | | 6v+2v+3= | | x^4+72x^2+94400=0 | | 2(4)+p=35 | | -16t(t+1)(t-5)=0 | | 2x+4(x-5)=2(x-4) | | 8m-11+2m-4=180 | | -x+3+14x=-6+4x+36 | | 2x+6-x-3=40 |